Perbandingan Keberagaman Makanan Berdasarkan Minimum Dietary Diversity For Women (MDDW) bagi Kesehatan Reproduksi Wanita - Yessy Syahradesi T; Fika Lestari; Yusnaini Yusnaini (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the comparison of food diversity based on the Minimum Dietary Diversity for Women (MDDW) for women's reproductive health. The method used is quantitative with a cross-sectional study approach. The results showed differences in food diversity among women of childbearing age in Kutacane City and Lawe Loning Aman Village, Southeast Aceh District. In conclusion, women of childbearing age in Kutacane City consume a variety of foods from more than five food groups compared to women of childbearing age in Lawe Loning Aman Village, who are less diverse in achieving minimum food intake. Therefore, it is hoped that health workers will provide education regarding food diversity in realizing women's reproductive health. Keywords: Diversity of Food, Reproductive Health, Women